King Geprek's Tiktok Content Strategy In Building Brand Awareness: An Analysis Of Islamic Business Ethics: Pemasaran Islami - Ainol Yaqin; FP Wulandari (CV Putra Publisher, 2026)
The development of social media, particularly TikTok, has driven changes in digital marketing strategies for micro, small, and medium enterprises (MSMEs). This study aims to analyze TikTok's content strategy in building brand awareness and examine its impact on business performance and its alignment with the principles of Islamic business ethics at King Geprek Sumberanyar Paiton. This study uses a qualitative approach with a case study method. Data collection was conducted through interviews, observation, and documentation, while data analysis was carried out through the stages of reduction, presentation, and drawing conclusions using triangulation techniques to maintain data validity. The results show that a content strategy that includes a consistent account identity, product visualization, transparency of the production process, and interaction with the audience is able to build brand awareness that includes brand recognition, brand recall, and brand exposure. This increase in brand awareness has an impact on improving business performance, as indicated by increases in sales, number of consumers, and turnover. In addition, the implemented content strategy also reflects the principles of Islamic business ethics, namely honesty (shiddiq), justice ('adl), and responsibility (amanah), which contribute to increasing consumer trust. This research shows that digital marketing through TikTok is not only effective in improving business performance but can also be carried out ethically in accordance with Islamic values.